COMBINED ANTIHYPERTENSIVE THERAPY IN METABOLIC SYNDROME - E. I. Mananko; E. A. Bushkova; E. M. Idrisova; A. I. Vengerovsky (Столичная издательская компания, 2016)
Aim. To compare effects of enalapril in combination with long-acting nifedipine or moxonidine on blood pressure (BP), myocardial mass and diastolic function of left ventricular, lipid and carbohydrate metabolism, platelet aggregation in patients with arterial hypertension (HT) and metabolic syndrome (MS).Material and methods. 50 patients with HT and MS were examined. 25 patients were treated with enalapril and long-acting nifedipine and 25 patients - with enalapril and moxonidine. 24-hour BP monitoring, echocardiography, anthropometry, lipid and carbohydrate metabolism estimation, platelet aggregation testing were performed before and 6 months after treatment.Results. Both combinations allowed to achieve target BP levels, provided cardioprotective and positive metabolic effects in most patients. The combination of enalapril and long-acting nifedipine had more significant antihypertensive effect and more prominently decreased the platelet aggregation induced by collagen. The combination of enalapril and moxonidine had more significant positive effects on carbohydrate metabolism and ADP-induced platelet aggregation.Conclusion. Enalapril in combination with long-acting nifedipine or moxonidine can be recommended for treatment of patients with HT and MS.